Vertical differences in species turnover and diversity of amphipod assemblages associated with coralline mats. (5th November 2016) - Bueno, M.; Tanaka, M.O.; Flores, A.A.V.; Leite, F.P.P.
Abstract: Environmental gradients are common in rocky shore habitats and may determine species spatial distributions at different scales. In this study, we tested whether environmental filtering affects amphipod assemblages inhabiting coralline algal mats at different vertical heights in southeastern Brazil. Samples obtained from the upper and lower zones of the infralittoral fringe were used to estimate mat descriptors (algal mass, sediment retention, organic matter contents, grain size and sediment sorting) and describe amphipod assemblages (abundance, species richness and diversity indices). Coralline algal mats and amphipod assemblages were similar between intertidal zones in several aspects. However, a more variable retention of sediment (positively related to algal mass), together with the accumulation of larger grains lower on the shore, likely provide higher habitat heterogeneity that hosts generally more diverse (both α- and β-diversity, as well as higher species turnover) amphipod assemblages in the lower intertidal zone. Poorer assemblages in the upper intertidal zone are dominated by omnivores, while carnivorous species are more often found in richer assemblages in the lower intertidal zone, as predicted by traditional niche theory. Highlights: Environmental stress imposes vertical gradients in rocky shores. Coralline mats were related to abiotic factors in lower but not in upper intertidal zones. Higher α- and β-diversity, and species turnover, were found in lower zones. Stress may influence diversity in upper intertidal zones, but stochasticity in lower intertidal zones. Low intertidal patches retaining coarse grains host more diverse assemblages.